Children of Peace - McIntyre, W. John (William John), 1951- (McGill-Queen's studies in the history of religion, 1994)
The Children of Peace, which existed from 1812 to 1890, was started by former Quakers from the United States who set up a utopian community near Toronto. With their propensity for fine architecture, music, and ritual, adherents to the sect attracted the attention of the religious, political, and social elites. Their leader and founder, David Willson, was one of the most prolific religious writers and theorists in Canada at the time. The Children of Peace sought to create a church where God spoke directly to all and where both Christians and Jews could find a home. McIntyre looks at life in the community and places the sect within its broader historical contexts. His examination of the community's buildings and artefacts provides insight into the beliefs and behaviour of its adherents. Children of Peace makes an important contribution to the growing field of religious and cultural history in Canada.